2022
DOI: 10.1007/s12011-022-03434-w
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Mitigates Ammonia-Induced Neurotoxicity by Suppressing Apoptosis, Immune Imbalance, and Gut Microbiota-Driven Metabolic Disturbance in Fattening Pigs

Abstract: Ammonia could be regarded as one detrimental pollutant with an acrid smell in livestock sheds. So far, the pig breeding industry became the main source of atmospheric ammonia. Previous literature demonstrated that excessive ammonia inhalation might cause a series of physiological damage to multiple organs. Unfortunately, the toxicity mechanisms of gaseous ammonia to the porcine nervous system need further research to elucidate. Selenium (Se) involves in many essential physiological processes and has a mitigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Choi et al [70] also found an increase in lateral lying pigs exposed to 15.35 ppm NH3 during summer. Exposure to high atmospheric NH3 increases NH3 level in the blood [58], leading to NH3 poisoning in which the secretion of excitatory neurotransmitters is inhibited making the animals less active [71]. Additionally, lying behavior has been linked to the health conditions of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al [70] also found an increase in lateral lying pigs exposed to 15.35 ppm NH3 during summer. Exposure to high atmospheric NH3 increases NH3 level in the blood [58], leading to NH3 poisoning in which the secretion of excitatory neurotransmitters is inhibited making the animals less active [71]. Additionally, lying behavior has been linked to the health conditions of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…After using enhanced chemiluminescence (ECL) chromogenic solution (Beyotime, Beijing, China) to treat the strip, chemical imaging system (Syngene G: box chemi XX9, UK) was used to detect the signal bands. Image J 18.0 software (National Institutes of Health, Bethesda, MD, USA) was used to measure the relative gray values [62,63]. The calculation formula was as follows:…”
Section: Western Blotmentioning
confidence: 99%